2011
DOI: 10.1126/science.1200508
|View full text |Cite
|
Sign up to set email alerts
|

A Packing Mechanism for Nucleosome Organization Reconstituted Across a Eukaryotic Genome

Abstract: Near the 5′ end of most eukaryotic genes, nucleosomes form highly regular arrays that begin at canonical distances from the transcriptional start site. Determinants of this and other aspects of genomic nucleosome organization have been ascribed to statistical positioning, intrinsically DNA-encoded positioning, or some aspect of transcription initiation. Here, we provide evidence for a different explanation. Biochemical reconstitution of proper nucleosome positioning, spacing, and occupancy levels was achieved … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

30
419
6
6

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 305 publications
(461 citation statements)
references
References 27 publications
30
419
6
6
Order By: Relevance
“…This research has provided insight into the importance of nucleosomal sequence preferences for chromatin organization (7), and has allowed for the creation, refinement, and testing of many models for predicting nucleosome positioning along genomes (8,9). The intrinsic nucleosome-DNA affinity of genomic sequences appears to play a significant role in vivo in positioning nucleosomes in certain regions of the genome, such as transcription start sites (TSSs) and origins of replication (7), alongside other effects like the presence of proteins that compete for the same DNA stretch or the action of chromatin remodelers (10,11).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This research has provided insight into the importance of nucleosomal sequence preferences for chromatin organization (7), and has allowed for the creation, refinement, and testing of many models for predicting nucleosome positioning along genomes (8,9). The intrinsic nucleosome-DNA affinity of genomic sequences appears to play a significant role in vivo in positioning nucleosomes in certain regions of the genome, such as transcription start sites (TSSs) and origins of replication (7), alongside other effects like the presence of proteins that compete for the same DNA stretch or the action of chromatin remodelers (10,11).…”
Section: Introductionmentioning
confidence: 99%
“…Most of these studies were conducted in vivo, and therefore do not allow for isolation of effects encoded into the genomic sequences. This body of research shows, however, that sequence effects alone are not generally sufficient to explain in vivo observations (11). An important role is also played by the active regulation of transcription.…”
Section: Introductionmentioning
confidence: 99%
“…More specifically, the isw2 and isw1 complexes contribute to the positioning of nucleosomes in intergenic regions or in the middle of genes, respectively, which suppresses cryptic, antisense transcription that would otherwise pose a risk of interfering with sense transcription (Whitehouse et al 2007;Tirosh et al 2010). The positioning and phasing of nucleosomes around transcription start sites in yeast, which frequently carry information in the form of histone variants and specific modifications, are brought about by the RSC complex in S. cerevisiae Zhang et al 2011). In fission yeast the CHDtype remodeler, Mit1, has been shown to be involved in aligning nucleosomal arrays with respect to promoter boundaries, a process termed nucleosome "phasing" (Lantermann et al 2010).…”
Section: Nucleosome Remodeling In Chromatin Assembly and Organizationmentioning
confidence: 99%
“…Nucleosome mapping in situ combined with biochemical studies has revealed that nucleosome positions determine access to DNA regulatory sequences essential to these processes (1,2). Nucleosome position is determined chiefly by DNA sequence and ATP-dependent chromatin remodeling factors (3)(4)(5). The nucleosome includes a linker DNA of variable length and a nucleosome core containing a histone octamer and 147 bp of DNA (6).…”
mentioning
confidence: 99%